Enhancing Teachers' Competence in Building Students' Numeracy in Grades K-3 - Patterson, Lynn; Xu, Yuejin (Frontiers in Education, 2020)
Supporting growth in problem solving is key to capacity development for both teachers and students. When teachers engage in rich academic conversations that inquire deeply into content and pedagogy, they have an opportunity to cultivate student capacity to engage in rich academic discourse, problem solving and mathematical learning. In this study, we examined an intensive professional development training intervention in which teacher participants learned to use and understand the Teaching Learning Community (TLC) approach, design and connect standards-based lessons, and nurture a mindset of learning and thinking like a problem solver among students and teachers alike. We further examined whether there were any differences in students’ MAP test scores over time among students whose teachers participated in the intervention and students whose teachers did not participate. Findings from the Analysis of Variance of students’ MAP test scores indicated that students whose teachers participated in the intervention demonstrated more growth in mathematical proficiency, particularly in Grade 3. Thus, implementing an intervention like the one described herein that provides the appropriate resources to teachers, education in the form of high-quality professional development, and an opportunity to collaborate with peers and experts can result in direct improvement to student achievement in math.